Max Lamb - Exercises in seating - Ryan, Zoë 1976- (The Art Institute of Chicago, 2018)
"One of the most exciting designers working today, Max Lamb (b. 1980) has received international acclaim for his innovative experiments with materials, craft, and technology. Drawn to the form of the chair and its relationship to the human body, Lamb has explored many different inventive outcomes in his ever-evolving Exercises in Seating project. This book investigates over a decade of creative practice with a focus on his interest in seating...from stone thrones to wood chairs and enameled-steel stools. In Lamb's own words, "A seat is very simple in function, but very complex in the many different characters, forms, and ideas it can express." Both retrospective and forward looking, this volume...created in collaboration with the artist...is the most thorough investigation of Lamb's work to date and features an exclusive interview with noted artist Ryan Gander in which the designer discusses his creative processes and goals"...
Titelblatt auf Seite 105. - "Max Lamb: Exercises in Seating was published in conjunction with an exhibition of the same title held at the Art Institute of Chicago, March 22-August 26, 2018"
Keywords: Lamb, Max -- 1980-; DESIGN / Furniture / bisacsh; DESIGN / Industrial / bisacsh; ART / Collections, Catalogs, Exhibitions / General / bisacsh; Chair design -- Exhibitions; DESIGN / Furniture; DESIGN / Industrial; ART / Collections, Catalogs, Exhibitions / General; Stuhl; Design; Ausstellungskatalog -- Art Institute of Chicago -- 22.03.2018-26.08.2018 -- Chicago, Ill.; Bildband